Pengaruh Kepemimpinan Transformasional Kepala Sekolah Terhadap Kinerja Guru - Sri Rahaju Supandi (JURNAL PENDIDIKAN DAN KEWIRAUSAHAAN, 2023)
This study aims to find out whether there is an influence of transformational leadership of principals on improving teacher performance. This research is motivated by the low performance of teachers both in terms of planning learning, implementing learning, and evaluating learning. To determine whether or not there is an influence between the transformational leadership of the principal on teacher performance, this study uses quantitative research where the data obtained from the results of the questionnaire. This study took place at SMPN 1 Banyuglugur with a population of 56 people. The types of data required in this study include primary data and secondary data. The data collection technique in this study is to use the Field Research method. Research instruments in the form of questionnaires filled out through the Google Form. The validity test of correlation data includes a normality test and a linearity test. The normality test was performed with the SPSS Version 20 for windows application with the formula One-Sample Kolmogorov-Smirnov Test. The result of the study is that the influence of the principal's transformational leadership on the performance of teachers and staff in schools is acceptable and there is a significant influence between the transformational leadership variables of the principal and the variables of teacher and staff performance at SMPN 1 Banyuglugur. Based on the results of the calculation of the correlation coefficient, there is a fairly strong influence, as well as the results of the calculation of the coefficient of determination show that the influence of the transformational leadership of the principal with the performance of teachers and staff in the school shows a positive and linear direction.